2006
DOI: 10.1111/j.1365-2125.2006.02577.x
|View full text |Cite
|
Sign up to set email alerts
|

When gatekeepers meet the sentinel: the impact of a prior authorization requirement for cefuroxime on the prescribing behaviour of community‐based physicians

Abstract: AimsPrior authorization (PA), the requirement of physicians to obtain pre-approval as a prerequisite for coverage, may decrease drug utilization via a 'sentinel effect', a decrease in utilization caused by external review of prescribing. The purpose of this study was to assess the affect a PA restriction had on the utilization patterns of cefuroxime tablets in a managed care organization (MCO) in Israel. MethodsPhysician prescribing patterns were evaluated by conducting a retrospective drug utilization analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 17 publications
(15 reference statements)
0
10
0
Order By: Relevance
“…Infectious disease specialists conducted lectures on the importance of restricting outpatient antibiotic use to family practitioners, ''Clalit Health Services'' implemented the supervision of specific antibiotic preparations, such as azithromycin, used by each doctor in the outpatient clinics of the northern district, and formal guidelines for the use of antibiotics for common infections encountered in outpatient clinics were issued by ''Clalit Health Services'' in 2005. The effects of these measures can be seen in terms of the prescription of cefuroxime in a number of outpatient clinics in Israel: when restrictions in the prescription of this antibiotic were applied for 3 months, cefuroxime prescriptions dropped from 8 to 1.2% during the restriction period and stabilized at 4.3% after the restriction period [6]. Another study conducted in military outpatient clinics in Israel showed a decline in the prescription of azithromycin following an educational intervention that consisted of issuing guidelines on indications for use [7].…”
Section: Discussionmentioning
confidence: 99%
“…Infectious disease specialists conducted lectures on the importance of restricting outpatient antibiotic use to family practitioners, ''Clalit Health Services'' implemented the supervision of specific antibiotic preparations, such as azithromycin, used by each doctor in the outpatient clinics of the northern district, and formal guidelines for the use of antibiotics for common infections encountered in outpatient clinics were issued by ''Clalit Health Services'' in 2005. The effects of these measures can be seen in terms of the prescription of cefuroxime in a number of outpatient clinics in Israel: when restrictions in the prescription of this antibiotic were applied for 3 months, cefuroxime prescriptions dropped from 8 to 1.2% during the restriction period and stabilized at 4.3% after the restriction period [6]. Another study conducted in military outpatient clinics in Israel showed a decline in the prescription of azithromycin following an educational intervention that consisted of issuing guidelines on indications for use [7].…”
Section: Discussionmentioning
confidence: 99%
“…One Spanish study found that removal of prior authorization for some topical immunosuppressive medicines (tacrolimus and pimecrolimus) was followed by a sharp increase in the number of prescriptions for such medicines . One study in Israel observed a sharp increase in the number of prescriptions of cefuroxime after removal of cefuroxime prior authorization . And one study in Canada found a sharp increase in the number of prescriptions of glitazones after removal of prior authorization …”
Section: Discussionmentioning
confidence: 99%
“…Thus, these findings complement the estimates from previous studies by providing the granularity that is needed to inform both the practice and legislative communities about the burden of prior authorization activities on primary care practices [ 19 ]. It is also important to consider that prior authorization requirements may yield benefits, such as cost savings to the system [ 20 ] or the promotion of rational prescribing trends [ 21 ], although to date, the literature on this point appears to be equivocal [ 2 , 22 - 27 ]. In light of the pivotal role of primary care now and in the future [ 28 - 30 ], the benefits and costs of prior authorization activities in primary care deserves further understanding and action, and primary care offices should be appropriately compensated for this work.…”
Section: Discussionmentioning
confidence: 99%